The relationship between total quality management practices and organizational sustainability in the context of industry 4.0: the mediating effect of innovative performance - Nasir, Aemin (2022)
The advent of the Fourth Industrial Revolution has motivated manufacturing companies across the globe to pursue organizational sustainability agendas. However, the obsoleteness of current organizational sustainability standards in the light of IR 4.0 has posed a challenge to companies in implementing relevant strategies to sustain a competitive edge. Although Total Quality Management (TQM) practices help organizations sustain global competitiveness, there is disagreement in the literature regarding practices that influences organizational sustainability in the context of IR 4.0. This study investigates the influential TQM soft practices on organizational sustainability in the context of IR 4.0 by exploring the relationship between TQM soft practices (i.e., leadership, customer focus, continuous improvement, employee empowerment, information and analysis) and innovative performance on sustainability in the context of Industry 4.0. It further investigates the mediating role of innovative performance on the relationship between TQM practices and organizational sustainability. The Systems theory and the European Foundation of Quality Model (EFQM) of excellence are the guiding theories employed to explain the relationship between the variables in the research model. A total of 281 owners/managers of ISO manufacturing firms, representing a response rate of 71.5%, participated in this study. Data were collected via self-administered questionnaires. PLS-SEM was used to analyze the data and test the hypotheses. Statistical results reveal that, except for leadership, TQM practices (i.e., customer focus, continuous improvement, employee empowerment, information and analysis) significantly influence sustainability. Furthermore, while innovative performance was found to be significantly related to organizational sustainability, it was also found to mediate the relationship between TQM practices (i.e., customer focus, continuous improvement, employee empowerment, information and analysis) and organizational sustainability in the context of Industry 4.0. Finally, theoretical and methodological contributions, managerial implications and recommendations for future research are discussed